RECOMBINANT 2C, 3A, 3B, AND 3D NON-STRUCTURAL PROTEINS OF FMDV - Mukantayev , K.N.; Shustov , A.V.; Tursunov , K.; Іnіrbay , B.; Adish , J.; Rаmanculov , E.M.; Mukanov , K.K. (Eurasian Journal of Applied Biotechnology, 2016)
The foot-and-mouth disease (FMD) is a highly contagious disease found in both agricultural and wild cloven-hoofed animals. The basic and effective method for preventing the emergence and spread of the infection is vaccination of susceptible livestock and creation of a buffer zone for the immunized animals. Identification of the infected animals ina herd of vaccinated animals is important for preventingFMD. In this paper, we have presented materials associated with obtaining 2C, 3A, 3B, and 3D recombinant non-structural proteins of the FMD virus (FMDV) and detecting their diagnostic properties by usingthe enzyme-linked immunosorbent assay (ELISA). On the basis of amino acid sequencing of the 2C, 3A, 3B, and 3D non-structural proteins of different types of FMDV,genes of the most immunogenic sites of the antigenswere selected. We designed genetic constructions containing genes of the 2C, 3A, 3B, and 3D non-structural proteins of FMDV. The pET32 vector was used as the expression plasmid. For ELISA, recombinant 2C, 3A, 3B, and 3D non-structural antigens of FMDV were obtained. The molecular mass of the 2C, 3A, 3B, and 3D recombinant non-structural antigens was 40, 45, 38, and 34 kDa, respectively.